Stable water isotope tracing through hydrological models for disentangling runoff generation processes at the hillslope scale - Windhorst, David; Kraft, Philipp; Timbe, E.; Frede, Hans-Georg; Breuer, Lutz; Justus Liebig University Giessen (My University, 2014)
Hillslopes are the dominant landscape components where incoming precipitation becomes groundwater, streamflow or atmospheric water vapor. However, directly observing flux partitioning in the soil is almost impossible. Hydrological hillslope models are therefore being used to investigate the processes involved. Here we report on a modeling experiment using the Catchment Modeling Framework (CMF) where measured stable water isotopes in vertical soil profiles along a tropical mountainous grassland hillslope transect are traced through the model to resolve potential mixing processes. CMF simulates advective transport of stable water isotopes 18O and 2H based on the Richards equation within a fully distributed 2-D representation of the hillslope. The model successfully replicates the observed temporal pattern of soil water isotope profiles (R2 0.84 and Nash-Sutcliffe efficiency (NSE) 0.42). Predicted flows are in good agreement with previous studies. We highlight the importance of groundwater recharge and shallow lateral subsurface flow, accounting for 50 and 16% of the total flow leaving the system, respectively. Surface runoff is negligible despite the steep slopes in the Ecuadorian study region.
Keywords: ddc:630